Estimating the Short-Run Poverty Impacts of the 2010–11 Surge in Food Prices - Ivanic, Maros; Martin, Will; Zaman, Hassan (2012)
Global food prices have increased substantially since mid-2010, as have prices in many developing countries. In this study we assess the poverty impact of the price changes between June and December 2010 in twenty-eight low and middle income countries. This is done by gathering detailed information on individual households' food production and consumption levels for thirty-eight agricultural and food commodities to assess the impacts on household welfare. This study estimates that this sudden food price surge increased the number of poor people globally, but with considerably different impacts in different countries. The heterogeneity of these impacts is partly related to the wide variation in the transmission of global prices to local prices and partly to differences in households' patterns of production and consumption. On balance, the adverse welfare impact on net buyers outweighs the benefits to net sellers resulting in an increase in the number of poor and in the depth of poverty. We estimate that the average poverty change was 1.1 percentage points in low income countries and 0.7 percentage points in middle income countries with a net increase of 44 million people falling below the $1.25 per day extreme poverty line.